التطور الدلالي في مصطلحات رياضة كرة القدم المعاصرة (جريدة الرياض نموذجا) ‏/‏ - سلمان، عبد الغني (Kulliyyah Ma'arif al-Wahy wa-al-'Ulum al-Insaniyah, al-Jami'ah al-Islamiyah al-'Alamiyah bi Maliziya, 2009)
This research aims at explaining recent developments in Arabic Language at the construction of modern terminologies of foot-ball game, whereby Arabic Language has been affected to some changes in Semantics. Therefore, its meanings eventually change from literal to technical terms of which we are today reading and viewing on television, radio and papers. It also examines the samples of terminologies and utterances used in games which had been critically and semantically addressed to explicate method of coined morphological interpolation with new meanings that occurred in connection with semantic development and its components such as specification, transference and publicity. Subsequently, particular emphasis is laid upon the most pivotal features of Arabic known as Derivation, a method showing a strong & actual relationship between literality & technicality. In the end, it moves up by abridging the new method in a diagram that obviously reflects the way in which a new Arabic scientific word is received. It, thereafter, rounds up with a conclusion, suggestions and bibliography.